Facet-based approach for the management of information multi points-of-view in product modeling. Issue 5 (29th July 2017) - Ouamer-Ali, Mohamed I.; Belkadi, Farouk; Laroche, Florent; Remy, Sébastien; Bernard, Alain
ABSTRACT: This paper presents a novel approach describing a framework that supports information representation and management along the product lifecycle. The aim is to provide a conceptual basis to build a multi-representation manager model which is useful for handling information sharing and interaction between experts from various domains, during the collaborative design project. The framework is based on the concept of facet that represents an elementary knowledge fragment of the product, as a combination of different information sources that are: product definition, business information, systems decomposition, and a temporal scale represented by the product lifecycle. The use of the facet concept for the integration of different points-of-view is described from a data modeling perspective. GRAPHICAL ABSTRACT: